2015
DOI: 10.2967/jnumed.115.163170
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal PET Imaging of Dynamic Metabolic Changes After Therapeutic Approaches of Induced Pluripotent Stem Cells, Neuronal Stem Cells, and a Chinese Patent Medicine in Stroke

Abstract: This study aimed to use spatiotemporal PET imaging to investigate the dynamic metabolic changes after a combined therapeutic approach of induced pluripotent stem cells (iPSCs), neuronal stem cells (NSCs), and Chinese patent medicine in a rat model of cerebral ischemia-reperfusion injury. Methods: Cerebral ischemia was established by the middle cerebral artery occlusion approach. Thirty-six male rats were randomly assigned to 1 of the 6 groups: control phosphate-buffered saline (PBS), Chinese patent medicine (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Positron emission tomography (PET), serving as the representative molecular imaging modality, enables noninvasive visualization of molecular changes during biological processes in vivo by utilizing radiolabeled molecules . PET imaging with [ 18 F]­fluoro-2-deoxyglucose ( 18 F-FDG), a glucose analog, has been used to detect subtle glucose metabolic alterations in vivo in a wide range of neurological diseases. , In this study, significantly higher 18 F-FDG uptake was observed in the ipsilateral ischemic brain area in the HPBZs-pretreated group than in the saline-pretreated MCAO group (Figure a,c, P < 0.05), suggesting that HPBZs pretreatment ameliorated cerebral glucose metabolic damage. Twenty-four hours after 18 F-FDG PET imaging, rat brains were extracted, sliced, and stained with 2,3,5-triphenyltetrazolium chloride (TTC).…”
mentioning
confidence: 61%
“…Positron emission tomography (PET), serving as the representative molecular imaging modality, enables noninvasive visualization of molecular changes during biological processes in vivo by utilizing radiolabeled molecules . PET imaging with [ 18 F]­fluoro-2-deoxyglucose ( 18 F-FDG), a glucose analog, has been used to detect subtle glucose metabolic alterations in vivo in a wide range of neurological diseases. , In this study, significantly higher 18 F-FDG uptake was observed in the ipsilateral ischemic brain area in the HPBZs-pretreated group than in the saline-pretreated MCAO group (Figure a,c, P < 0.05), suggesting that HPBZs pretreatment ameliorated cerebral glucose metabolic damage. Twenty-four hours after 18 F-FDG PET imaging, rat brains were extracted, sliced, and stained with 2,3,5-triphenyltetrazolium chloride (TTC).…”
mentioning
confidence: 61%
“…Cerebral ischemic stroke suppresses glucose metabolism in the brain, 12,42 and low glucose metabolism is closely related to mood disorders. 10,43,44 To examine whether MOOs influenced poststroke cerebral glucose metabolism, we performed 18 F-FDG PET-CT scan in PSD rats and quantified the standard uptake value (SUV) of 18 F-FDG.…”
Section: Moos Improve Glucose Metabolism and Restores Synapse Activmentioning
confidence: 99%
“…Spinal cord injury patients were transplanted with SPIO-labeled autologous bone marrow CD34 + cells, and some of them showed a persistent hypointense signal around the lesion site on MRI ( Callera and de Melo, 2007 ). Zhang et al used spatiotemporal PET imaging to observe dynamic metabolic changes after iPSC transplantation in stroke patients and found that iPSCs may differentiate into a more specific cell type before improving recovery from cerebral injury ( Zhang et al, 2015a ). Moreover, cerebral blood flow can be monitored via simultaneous [ 15 O] H 2 O PET/MRI after stroke ( Werner et al, 2015 ).…”
Section: Transplantation Of 3d Brain Organoid Tissue For Poststroke Repairmentioning
confidence: 99%